Multi-objective optimization of marine nuclear power secondary circuit system based on improved multi-objective particle swarm optimization algorithm - Zhao, Jiarui; Li, Yanjun; Bai, Jinfeng; Ma, Lin; Shi, Changwei; Zhang, Guolei; Shi, Jianxin (Progress in nuclear energy (New series), 2023)
The mathematical model for the main equipment and auxiliary equipment of the marine nuclear power secondary circuit system and the system heat balance calculation model are established. A complete mathematical model of the secondary circuit system is obtained by coupling the above model. In addition, an adaptive multi-objective particle swarm optimization algorithm based on angle penalized distance (AMOPSO-APD) for complex and strong coupling marine nuclear power system is obtained by introducing the angle penalized distance and the adaptive adjustment strategy of algorithm parameters based on convergence factor in the MOPSO algorithm. By optimizing the benchmark test problems to compare the performance of the improved algorithm, the original one, and the NSGA-II algorithm. It is discovered that the improved algorithm has greatly enhanced search capability and optimization efficiency. Sensitivity analysis is used to choose parameters for optimization that have a significant impact on the equipment structure and system performance, such as the secondary circuit saturated steam pressure, the U-tube outer diameter, and the coolant flow velocity in U-tube. Satisfying the safety, performance, and structure constraints, taking the lightest weight, minimum volume, and highest effective efficiency of the secondary circuit system as the optimization objectives, the optimal design for the system is carried out with the AMOPSO-APD algorithm, the Pareto optimal solutions and Pareto front are obtained, and the TOPSIS method is used to choose the compromise optimization scheme. In the optimized secondary circuit system, the weight is reduced by 10.57%, the volume is reduced by 13.68%, and the effective efficiency is increased by 4.26%.